2018
DOI: 10.1111/acer.13817
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Choline Supplementation on Neurological, Cognitive, and Behavioral Outcomes in Offspring Arising from Alcohol Exposure During Development: A Quantitative Systematic Review of Clinical and Preclinical Studies

Abstract: Prenatal alcohol exposure results in cognitive, behavioral, and neurological deficits in offspring. There is an urgent need for safe and effective treatments to overcome these effects. Maternal choline supplementation has been identified as a potential intervention. Our objective was to review preclinical and clinical studies using choline supplementation in known cases of fetal alcohol exposure to determine its effectiveness in ameliorating deficits in offspring. A systematic search of 6 electronic databases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 86 publications
(179 reference statements)
2
30
0
Order By: Relevance
“…In pregnancy, higher frequencies and amounts of binge drinking have also been reported than in nonpregnant women [135]. From the evidence-base, it is increasingly apparent that choline can attenuate some of the neurological damage associated with fetal alcohol syndrome [31,98,99,[101][102][103][104]113,119,129]. Women need to be better informed that there is no known safe level of alcohol consumption when they might be or are pregnant.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In pregnancy, higher frequencies and amounts of binge drinking have also been reported than in nonpregnant women [135]. From the evidence-base, it is increasingly apparent that choline can attenuate some of the neurological damage associated with fetal alcohol syndrome [31,98,99,[101][102][103][104]113,119,129]. Women need to be better informed that there is no known safe level of alcohol consumption when they might be or are pregnant.…”
Section: Discussionmentioning
confidence: 99%
“…Data from animal models show that higher intakes of choline during gestation and the perinatal period can protect against brain damage and cognitive/neurological declines associated with epilepsy and certain hereditary conditions, such as Down Syndrome and Rett Syndromes [30]. Additionally, a review collating evidence from 22 human clinical and preclinical studies concluded that choline supplementation has the potential to ameliorate some of the behavioral, cognitive, and neurological deficits observed in offspring exposed to alcohol in utero [31].…”
Section: Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…One potential explanation for this finding is that guidelines and standards for multicenter studies are just emerging, and there has yet to be any reporting recommendations specific to a preclinical multicenter design. Nonetheless, compared to previous reporting assessments of single-centered preclinical studies [32, 33], the completeness of reporting for the twelve preclinical multicenter studies was appreciably higher.…”
Section: Discussionmentioning
confidence: 55%
“…It also results in epigenetic modifications, altered preimplantation embryo development and placental function (Kalisch-Smith and Moritz 2018). A recent systematic review of clinical and preclinical studies indicates that dietary supplementation with choline partially reverses the effects of alcohol on offspring health (Akison et al 2018). The concentration of alcohol and altered milieu experienced by the gametes and the early preimplantation embryo in the reproductive tract requires further investigation such that appropriate models can be developed to interrogate the effectiveness of novel interventions (Kalisch-Smith and Moritz 2018).…”
Section: Speakers: Mary Wlodek Michelle Lane Patrick Western Karenmentioning
confidence: 99%